The Female Athlete Triad: A Metabolic Phenomenon - Anne B. Loucks (Universidad de Costa Rica, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> The Female Athlete Triad (Triad) is a syndrome in which low energy availability triggers a broad range of endocrine mechanisms that conserve energy expenditure, and thereby impairs reproductive and skeletal health. Energy availability is the amount of dietary energy remaining after exercise training for all other physiological functions each day. The specific kind of reproductive dysfunctions caused by low energy availability are functional hypothalamic menstrual disorders. To ensure that affected athletes receive appropriate care, endocrine tests are required to diagnose these disorders by the exclusion of other types of menstrual disorders unrelated to the Triad. In addition, low energy availability impairs skeletal health by uncoupling bone turnover, in which the rate of bone resorption increases while the rate of bone formation declines. The result is a progressive loss or failure to accrue bone mass, which increases the risks of stress fractures and osteoporosis. Low energy availability originates in one or more of three sources: restrictive eating disorders, especially anorexia nervosa; intentional efforts to lose body weight or body fat to improve athletic performance or appearance; and the inadvertent suppression of appetite by exercise and diets containing a high percentage of carbohydrates. It is necessary to know the origin of low energy availability in a particular athlete in order to intervene effectively with her. The key behavior modification for preventing and treating the Triad is to increase energy availability, either by increasing dietary energy intake, reducing exercise energy expenditure, or both. Guidelines for doing so are provided. <!--[if gte mso 9]>